Transnational terrorism, organized crime and peace-building: human security in the western Balkans - Benedek, Wolfgang. (ed.) (New York, 2010)
This fascinating volume investigates the role of transnational terrorism and criminal organizations in the peace-building process in the Western Balkans. It maps organized crime and terrorism in the region and highlights the close links that have developed between organized crime and state institutions during and after the wars. Benedek and his team demonstrate how weak states in post-conflict situations can be strengthened. The international community, from the outside, and civil society, from within, play a role as counterforces to identified threats. They can strengthen the rule of law, transitional justice, control over money laundering, the promotion of human rights and democracy, as well as furthering reconciliation attempts and peace-building. This book identifies their good practices, successes and failures.
Keywords: Human security-Countries of western Balkans